Pengaruh Variasi Suhu Sintesis Kristal Hidroksiapatit (HAp) terhadap Diameter Kristal yang Disintesis dari Precipitated Calciul Carbonate (PCC) Kulit Telur Ayam Secara Hidrotermal - Faradila, Harfiah; Yelmida, Yelmida; Fadli, Ahmad (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2025)
In Indonesia, the incidence of bone fractures in 2018 was approximately nine million, with various types of fractures and causes. Hydroxyapatite, Ca₁₀(PO₄)₆(OH)₂ or HAp, is one of the bioceramics commonly used in biomedical applications due to its composition, it has biocompatible and osteoconductive properties and integrates well with bone. The aim of this research is to determine the time required to produce hydroxyapatite (HAp) diameter through the growth of HAp crystals from chicken egg shells. The aim of this study is to examine the effect of reaction temperature (120 and 140°C) and hydrothermal reaction time (1, 3, 4, 5, 7, and 9 hours) on the crystal growth of apatite compounds from Precipitated Calcium Carbonate (PCC) of chicken eggshells. Technically, PCC has advantages such as small particle size (microscale) and homogeneity. HAp is made from PCC and diammonium hydrogen phosphate (NH₄)₂HPO₄ as a phosphate source in the hydrothermal vessel.The HAp produced is characterized using X-ray diffraction (XRD). The HAp crystals obtained are hexagonal in shape with significant precision in the crystalline details of Holly Springs Hydroxyapatite. The good condition process to produced highest crystal diameter of HAp was achieved at a temperature of 140°C, measuring 33.29 nm, with a reaction time of 9 hours. Thus, the higher the reaction temperature and the longer the synthesis time, the larger the HAp crystal diameter